Strategi Pembentukan Karakter Keagamaan Peserta Didik di SMA Kota Tenggarong - Alim, Nur (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2017)
This study departs from the low religious character of learners is one of the problems that occur in schools. This is due to two factors, namely, internal and external. To overcome these obstacles required a strategy in the formation of a systematic religious character that can be â€ammunitionâ€ in shaping the religious character of learners so that it can make learners become our human beings. The purpose of this study wanted to know about the strategy of character formation, the implementation of character formation and inhibiting factors and solutions in the formation of religious character of learners in high school Tenggarong. Research method in this research use field research type (field work research) with qualitative approach. The data collection is observation, semi-structured interviews and documentation. While the technique of data analysis using data reduction, data presentation and conclusion. The result of research strategy of religious character formation of learners in Tenggarong High School is 1) Self-development which is not programmed include routine activity, spontaneous activity and exemplary already compatible with document of Ministry of National Education about character design of character education. 2) Implementation of religious character formation in routine activity shows significant similarity that is, class picket, worship, pray before and after learning in class and social service. As for spontaneous activity, that is, visiting the sick, throwing the garbage in its place, engulfing the argument. While the exemplary activities that is, by speaking polite, obey the order, dressed neatly and clean, and behave courteously. Although the spontaneous and exemplary activities have been implemented but not yet optimal. Due to the unavailability of all indicators on spontaneous and exemplary activities. 3) Factors inhibiting the formation of religious character that is, coming from the educators and education, the people who live around the school environment and the control of the competent. The solution in overcoming obstacles in the implementation of the formation of religious character is, by improving the quality of principals, educators and education, improvement of facilities and infrastructure, study appeal and cooperate with the competent.